SCHOOL LEADERS MATTER: THE ROLE OF SCHOOL PRINCIPALS IN IMPLEMENTING UDL IN K-12 SCHOOLS - Stasiunaitiene, Egle; Nedzinskaite-Maciuniene, Rasa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The aim of this article is to fill the gap of scientific evidence on the role of school principals in implementing UDL in K-12 schools. The case study research was conducted, and field notes were taken from one district in Lithuania, which has been implementing UDL in its schools since 2019. The data for this research was gathered using in-depth semi-structured interviews involving 5 participants. Based on an inductive thematic analysis, six themes emerged: initiating UDL as an organisational change; planning and ensuring the development of staff competencies related to didactic decisions; initiating changes in teachers’ attitudes; motivating teachers to take leadership at the classroom level; promoting the sharing of experiences among teachers (successes and failures); and establishing and maintaining an organisational culture. The discussion explores the implications of the findings for the successful and effective application of UDL in K-12 schools.